KETETAPAN MPR DALAM HIRARKI PERATURAN PERUNDANG.UNDANGAN - A.Rosyid Al Atok (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2012)
MPR Decree was in hierarchical manner betweenl945 and theAct which in theory in the group of legal norms Staats grund gesetz (Rules of the State/State Basic Rules). MPR Decree under the 1945 Constitutionis a consequence of the position of the MPR as executor of full sovereignty of the people and the country's top institutions. However, 1945 Constitution amendment no longer determinethe MPR as executor of full sovereignty of the people. Moreover, MPR are no longer the highest state institution. Therefore, it has implications for the existence of the Legislative Actin the hierarchy of legislation. MPRS Decree No. XXA4PRS/1966 and MPR Decree No.IIL&IPR/2000 put MPR Decree in the second place after 1945 Constitution. LawNo. l0 of 2004 does not recognize the MPR decree as one type of legislation. Law No.12 of 20 i 1 put back MPR decree as one type of legislation. This paper attempts to discuss the rationale of the dynamic development of MPR Decree position in the hierarchy of legislation before the Amendment of 1945 Constitution to the promulgation of Law No. l2 of 20 I I , after the Amendment of I 945 Constitution.